2019
DOI: 10.1038/s41598-019-38582-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tinnitus after vestibular schwannoma surgery

Abstract: We designed a prospective study to evaluate changes in tinnitus after vestibular schwannoma (VS) surgery. Subjects included 41 patients who were diagnosed with a VS and underwent translabyrinthine microsurgery (TLM) between January 2015 and May 2016. All patients underwent related examinations and were asked to answer the Tinnitus Handicap Inventory (THI) scale and a visual analog scale (VAS) of tinnitus severity both pre- and postoperatively. Of the 41 patients, 31 (75.6%) suffered from tinnitus before surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…1 Tinnitus is a common symptom (>50%) in patients with vestibular schwannomas (Figure 11), and its preoperative severity can predict the postoperative prognosis of these patients with louder tinnitus associated with worse prognoses and poorer quality of life than patients with low-intensity tinnitus. 30 Vestibular schwannoma is a benign tumor of the vestibulocochlear nerve that typically arises from within the IAC and extends to the cerebellopontine angle. Unilateral and nonhereditary forms usually occur in middle-aged patients, while the bilateral form is described in patients younger than 21 years old with neurofibromatosis type 2.…”
Section: Vestibular Schwannomamentioning
confidence: 99%
See 1 more Smart Citation
“…1 Tinnitus is a common symptom (>50%) in patients with vestibular schwannomas (Figure 11), and its preoperative severity can predict the postoperative prognosis of these patients with louder tinnitus associated with worse prognoses and poorer quality of life than patients with low-intensity tinnitus. 30 Vestibular schwannoma is a benign tumor of the vestibulocochlear nerve that typically arises from within the IAC and extends to the cerebellopontine angle. Unilateral and nonhereditary forms usually occur in middle-aged patients, while the bilateral form is described in patients younger than 21 years old with neurofibromatosis type 2.…”
Section: Vestibular Schwannomamentioning
confidence: 99%
“…In the presence of unilateral continuous tinnitus with unilateral or asymmetric hearing loss, audiometry and MRI are usually performed to evaluate for a vestibular schwannoma 1 . Tinnitus is a common symptom (>50%) in patients with vestibular schwannomas (Figure 11), and its preoperative severity can predict the postoperative prognosis of these patients with louder tinnitus associated with worse prognoses and poorer quality of life than patients with low‐intensity tinnitus 30 …”
Section: Differential Diagnosis and Imaging Findings In Continuous Ti...mentioning
confidence: 99%
“…Considering symptom control, most respondents held that surgery has an unpredictable effect on tinnitus. Noteworthy, Wang et al 17 showed that microsurgical VS resection led to Tinnitus Handicap Index reduction in up to 77% of cases. Most surgeons in Italy and in North America considered that VS surgical removal led to a reduction or even to the resolution of preoperative dizziness.…”
Section: Surgerymentioning
confidence: 99%
“…aeruginosa 2.5 2.5 16 E . coli 1.25 2.5 S. aureus 2.5 2.5 TiO 2 /ZnO/4A 10–50 E. coli 1 2 33 S. aureus 2 3 TiO 2 /ZnO E . coli 5 10 46 S. aureus 5 10 K. pneumoniae 5 10 MRSA 0.15 0.30 ZnO-CuO Length: 8.126 and diameter: 7.515 P .…”
Section: Introductionmentioning
confidence: 99%